The Implications of Non-Domestication of Kampala Convention to the Protection of the Internally Displaced Persons (IDPs) in Nigeria - Tasiu Magaji (International Studies Journal)
This paper examines the implications of the non-domestication of the Kampala Convention on the protection of internally displaced persons (IDPs) in Nigeria. The Kampala Convention is a regional treaty aimed at protecting and providing assistance to IDPs, and Nigeria signed the convention in 2009. However, the convention has not been domesticated into Nigerian law, leaving IDPs particularly vulnerable to extreme challenges such as forced displacement, loss of shelter and assets and discrimination. Using a qualitative research approach where primary and secondary data are utilized. Primary data consists relevant reports, whereas the secondary data covers relevant documents and legal frameworks. The paper articulates the importance of domestication of the convention to the protection of IDPs in Nigeria. The paper argues that domestication will not only provide tangible legal protection for IDPs, but it will also promote accountability and transparency in the protection, assistance, and recovery efforts organized by state agencies and non-governmental organizations alike. The paper concludes that the domestication of the Kampala Convention is pivotal to ensure that IDPs in Nigeria can be adequately protected and given access to necessary assistance. The paper further recommends government institutions to work towards domestication and implementation of the convention to address the plight of IDPs in Nigeria.